Early Bronze Age copper smelting furnaces from Chrysokamino, Crete - Philip P. Betancourt; Susan C. Ferrence; Alessandra Giumlia-Mair (UISPP Journal)
During the Early Bronze Age, before the expansion in copper mining and distribution of this metal from Cyprus, Aegean metal production relied especially on local ores. An example of this industry has been excavated from only a few sites in the Aegean. One of these smelting workshops has been excavated at Chrysokamino in eastern Crete. Its smelting furnaces provide a good example of the technology in use at early copper production centers in the Aegean region.